Bipolar soft package battery structure and preparation method thereof
By filling the separator of the gel electrolyte and the positive electrode layer and the negative electrode layer infiltrated by the gel electrolyte precursor, combined with the stacking structure of the first unit, the second unit and the third unit, the interface and seal of the bipolar soft-pack battery are solved. The problem of efficiency of charging and discharging and low-cost production is achieved.
Patent Information
- Application Number
- CN202411425542.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-13
- Publication Date
- 2024-12-20
AI Technical Summary
The existing bipolar soft-pack battery structures have interface problems, sealing problems and high cost problems, making it difficult to effectively improve energy density and safety performance.
Using a separator filled with gel electrolyte and a positive electrode layer and an anode layer that is infiltrated by the gel electrolyte precursor, a bipolar soft-pack battery is formed through the stacking structure of the first unit, the second unit and the third unit, thereby avoiding the electrolyte. flow and ion short circuits simplify the preparation process and reduce costs.
It realizes normal charging and discharging of bipolar soft-pack batteries, improves interface contact effect, avoids electrolyte fluid flow and ion short circuit problems, reduces preparation costs, and is suitable for large-scale industrial production.
Smart Images

Figure CN119170887A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrochemical energy storage, and in particular relates to a bipolar soft-pack battery structure and a preparation method thereof. Background Art
[0002] In recent years, the world is facing energy shortage and environmental pollution, which are two major problems that need to be solved urgently. The development of new energy vehicles and the country's strong support for the new energy industry have made it possible to solve these two major problems. As the market's requirements for lithium battery energy density and safety performance are getting higher and higher, the improvement of energy density and safety performance are the focus of attention in the industry. The use of gel electrolyte can avoid the potential risk of electrolyte combustion when using liquid electrolytes. In addition, the immobility of the electrolyte makes it easier to achieve a bipolar structure, greatly reducing the risk of ion short circuits in the battery.
[0003] At present, most of the research on bipolar batteries is focused on solving the problem of ion short circuit. Patent application CN117613193A discloses a sodium ion bipolar solid-state battery without a negative electrode, which realizes the preparation of sodium ion batteries without introducing negative electrode plates, and also avoids safety issues such as battery failure caused by battery short circuit and gas production. Patent application CN116365005A discloses a bipolar battery sealing frame and a bipolar sealed battery, wherein the battery cells of the bipolar battery are thinner, and more battery cells are stacked and connected in series per unit volume, thereby improving the energy density and power density of the bipolar battery. Patent application CN115483360A discloses a method for preparing a sodium ion bipolar battery, which achieves sealing by coating a sealant on the edge of the current collector.
[0004] Theoretically, it is feasible to avoid ion short circuit by using all-solid-state electrolytes. However, the interface problems and high cost problems of all-solid-state batteries are still difficult to solve. It is relatively difficult to achieve a sealing effect by using sealants. The uniformity and swelling of the sealant will affect the sealing effect. Summary of the invention
[0005] The embodiments of the present invention provide a bipolar soft-pack battery structure and a preparation method thereof, aiming to solve the interface problems, sealing problems, high cost and other problems existing in the existing bipolar soft-pack battery structure.
[0006] To achieve the above object, on the one hand, an embodiment of the present invention provides a bipolar soft-pack battery structure, comprising a first unit, at least one second unit, and a third unit, wherein the second unit is arranged between the first unit and the third unit;
[0007] The first unit includes a first current collector and a first positive electrode layer that are arranged in contact with each other, and the first positive electrode layer is arranged close to the second unit;
[0008] The second unit includes a first separator, a first negative electrode layer, a second current collector and a second positive electrode layer which are sequentially abutted; the first separator abuts the first positive electrode layer, and the second positive electrode layer is arranged close to the third unit;
[0009] The third unit comprises a second separator, a second negative electrode layer and a third current collector which are sequentially abutted; the second separator abuts the second positive electrode layer;
[0010] The first separator and the second separator are both separators filled with gel electrolyte.
[0011] As a preferred embodiment, the first current collector, the second current collector and the third current collector are all one of an aluminum foil current collector, a stainless steel foil current collector, a titanium foil current collector or a copper-aluminum composite foil current collector.
[0012] As a preferred embodiment, the thickness of the first current collector, the thickness of the second current collector and the thickness of the third current collector are all 5 μm to 500 μm.
[0013] As a preferred embodiment, the thickness of the first positive electrode layer and the thickness of the second positive electrode layer are both 20 μm to 2000 μm.
[0014] As a preferred embodiment, the first positive electrode layer and the second positive electrode layer both contain the following components by mass percentage: 60% to 96% positive electrode active material, 2% to 5% first conductive agent, 2% to 5% first binder and 0% to 30% first solid electrolyte.
[0015] As a preferred embodiment, when the bipolar soft-pack battery structure is a lithium-ion battery structure, the positive electrode active material is one or a mixture of at least two of ternary lithium, lithium iron phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium cobalt oxide, lithium manganese oxide and lithium-rich manganese-based materials;
[0016] When the bipolar soft-pack battery structure is a sodium ion battery structure, the positive electrode active material is one of polyanions, Prussian blue and oxides, or a mixture of at least two of them.
[0017] As a preferred embodiment, the first conductive agent is one or a mixture of at least two of Super P, LI-2080, 350G, acetylene black, carbon fiber VGCF, carbon nanotubes CNTs, Ketjen black, graphite conductive agent and graphene;
[0018] The first binder is one or a mixture of at least two of polyvinylidene fluoride (PVDF) and its modified materials, polyethylene oxide (PEO) and its modified materials, polymethyl methacrylate (PMMA) and its modified materials, polytetrafluoroethylene (PTFE), sodium carboxymethyl cellulose (CMC) and its modified materials, lithium carboxymethyl cellulose (CMC) and its modified materials, styrene-butadiene rubber (SBR) and its modified materials, and polyvinyl alcohol (PVA) and its modified materials;
[0019] The first solid electrolyte is one of an oxide solid electrolyte, a NASICON solid electrolyte, a sulfide solid electrolyte and a halide solid electrolyte, or a mixture of at least two of them.
[0020] As a preferred embodiment, the thickness of the first negative electrode layer and the thickness of the second negative electrode layer are both 20 μm to 2000 μm.
[0021] As a preferred embodiment, the first negative electrode layer and the second negative electrode layer both contain the following components by mass percentage: 60% to 96% negative electrode active material, 2% to 5% second conductive agent, 2% to 5% second binder and 0% to 30% second solid electrolyte.
[0022] As a preferred embodiment, the negative electrode active material is one or a mixture of at least two of metallic lithium, graphite, silicon-based negative electrode, lithium titanate, metallic sodium, hard carbon or soft carbon;
[0023] The second conductive agent is one or a mixture of at least two of Super P, LI-2080, 350G, acetylene black, carbon fiber VGCF, carbon nanotubes CNTs, Ketjen black, graphite conductive agent and graphene;
[0024] The second binder is one or a mixture of at least two of polyvinylidene fluoride (PVDF) and its modified materials, polyethylene oxide (PEO) and its modified materials, polymethyl methacrylate (PMMA) and its modified materials, polytetrafluoroethylene (PTFE), sodium carboxymethyl cellulose (CMC) and its modified materials, lithium carboxymethyl cellulose (CMC) and its modified materials, styrene-butadiene rubber (SBR) and its modified materials, and polyvinyl alcohol (PVA) and its modified materials;
[0025] The second solid electrolyte is one or a mixture of at least two of an oxide solid electrolyte, a NASICON solid electrolyte, a sulfide solid electrolyte and a halide solid electrolyte.
[0026] As a preferred embodiment, the thickness of the first separator and the thickness of the second separator are both 5 μm to 500 μm.
[0027] As a preferred embodiment, both the first separator and the second separator include a separator matrix and a gel electrolyte filled in the separator matrix.
[0028] As a preferred embodiment, the diaphragm matrix is one or a mixture of at least two of a PP diaphragm matrix, a PE diaphragm matrix and a glass fiber diaphragm matrix;
[0029] The gel electrolyte is one of a polyacrylonitrile (PAN)-based gel electrolyte, a polymethyl methacrylate (PMMA)-based gel electrolyte, or a polyvinylidene fluoride (PVDF)-based gel electrolyte.
[0030] As a preferred embodiment, the electrolyte used in the bipolar soft-pack battery structure is a sodium ion gel electrolyte or a lithium ion gel electrolyte.
[0031] As a preferred embodiment, the length of the first negative electrode layer / the second negative electrode layer is 0.2 mm to 3 mm longer than the length of the first positive electrode layer / the second positive electrode layer, and the width of the first negative electrode layer / the second negative electrode layer is 0.2 mm to 3 mm wider than the width of the first positive electrode layer / the second positive electrode layer;
[0032] The length of the first separator / the second separator is 0.2 mm to 3 mm longer than the length of the first negative electrode layer / the second negative electrode layer, and the width of the first separator / the second separator is 0.2 mm to 3 mm wider than the width of the first negative electrode layer / the second negative electrode layer.
[0033] On the other hand, an embodiment of the present invention also provides a method for preparing the bipolar soft-pack battery structure, which comprises at least the following steps: in an inert gas atmosphere, immersing the diaphragm matrix in a gel electrolyte precursor, and after the diaphragm matrix is soaked, taking out the diaphragm matrix and encapsulating it to obtain an encapsulated diaphragm matrix; heating the encapsulated diaphragm matrix to obtain a first diaphragm / second diaphragm.
[0034] As a preferred embodiment, the inert gas is argon; the packaging is performed by an aluminum-plastic film; the heating is performed at 70°C to 85°C for 2h to 3h, preferably at 70°C for 2h. By heating, the gel electrolyte precursor is polymerized to form a gel electrolyte. Infiltration generally refers to that the diaphragm matrix is fully filled with the gel electrolyte precursor.
[0035] As a preferred embodiment, the method for preparing the bipolar soft-pack battery structure further includes the following steps: preparing a first unit: welding a first electrode tab on one side of a first current collector, and providing a first positive electrode layer on the other side of the first current collector to obtain a first unit;
[0036] Prepare a second unit: arrange a second positive electrode layer on one side of a second current collector, arrange a first negative electrode layer on the other side of the second current collector, and arrange a first separator on the side of the first negative electrode layer away from the second current collector to obtain a second unit;
[0037] Prepare a third unit: weld a second electrode tab on one side of a third current collector, arrange a second negative electrode layer on the other side of the third current collector, and arrange a second separator on the side of the second negative electrode layer away from the third current collector to obtain a third unit;
[0038] The first unit, the second unit and the third unit are stacked in sequence, the first separator is in contact with the first positive electrode layer, the second separator is in contact with the second positive electrode layer, and then packaged and heated to obtain a bipolar soft-pack battery structure.
[0039] As a preferred embodiment, the packaging is performed by an aluminum-plastic film; the heating is performed at 70° C. to 85° C. for 2 h to 3 h, preferably at 70° C. for 2 h.
[0040] As a preferred embodiment, the first positive electrode layer, the second positive electrode layer, the first negative electrode layer and the second negative electrode layer are all self-supporting dry electrode films.
[0041] The present application adopts a first diaphragm and a second diaphragm, and obtains a bipolar soft-pack battery structure by stacking the first unit, the second unit and the third unit, forming an internal structure composed of the first unit-(second unit) n-third unit (n≥1 and n is an integer), and the electrolyte adopts a gel electrolyte, and the flow of the electrolyte will not occur, avoiding the problem of ion short circuit when using a liquid electrolyte. The first diaphragm, the second diaphragm, and the positive and negative electrode layers of each unit are fully infiltrated with a gel electrolyte precursor, so that there is no need to seal and separate the two adjacent current collectors (i.e., the first current collector of the first unit and the second current collector close to the first unit, the two adjacent second current collectors, and the second current collector close to the third unit and the third current collector) and there is no need to seal between the two adjacent battery cells, with good interface contact, and can achieve normal charging and discharging of the battery. The preparation method of the structure of the present application is simple, the preparation cost is low, and it is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0043] Figure 1 1 is a schematic structural diagram of a bipolar soft-pack battery structure according to an embodiment of the present invention;
[0044] Figure 2 for Figure 1 Schematic diagram of the cross-sectional structure of the first diaphragm. DETAILED DESCRIPTION
[0045] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0046] It should be noted that if the embodiments of the present invention involve directional indications (such as up, down, left, right, front, back, top, bottom...), the directional indications are only used to explain the relative position relationship, movement status, etc. between the components in a certain specific posture. If the specific posture changes, the directional indication will also change accordingly.
[0047] In this application, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0048] It should be noted that when an element is referred to as being "fixed to" or "disposed on" another element, it may be directly on the other element or there may be an intermediate element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be an intermediate element at the same time.
[0049] In addition, if there are descriptions involving "first", "second", etc. in the embodiments of the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or suggesting their relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in the field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention. The raw materials used in the embodiments of this application are all commercially available materials.
[0050] On the one hand, if Figure 1 to Figure 2 As shown, an embodiment of the present invention provides a bipolar soft-pack battery structure, including a first unit 10, at least one second unit 20, and a third unit 30, wherein the second unit 20 is disposed between the first unit 10 and the third unit 30;
[0051] The first unit 10 includes a first current collector 11 and a first positive electrode layer 12 which are arranged in contact with each other, and the first positive electrode layer 11 is arranged close to the second unit 20;
[0052] The second unit 20 includes a first separator 21, a first negative electrode layer 22, a second current collector 23 and a second positive electrode layer 24 which are sequentially abutted; the first separator 21 abuts the first positive electrode layer 12, and the second positive electrode layer 24 is arranged close to the third unit 30;
[0053] The third unit 30 includes a second separator 31, a second negative electrode layer 32 and a third current collector 33 which are sequentially abutted; the second separator 31 abuts against the second positive electrode layer 24;
[0054] The first separator 21 and the second separator 31 are both separators filled with gel electrolyte 40 .
[0055] The present application adopts a first diaphragm and a second diaphragm, and obtains a bipolar soft-pack battery structure by stacking a first unit, a second unit and a third unit, forming an internal structure composed of a first unit-(second unit)n-third unit (n≥1 and n is an integer, that is, at least one second unit is set), and the electrolyte adopts a gel electrolyte, and the flow of the electrolyte will not occur, thereby avoiding the problem of ion short circuit when using a liquid electrolyte.
[0056] The number of stacked second units can be set according to actual needs, and can be one, two, three, four, five, or even more. Between two adjacent second units, the second positive electrode layer of the previous second unit abuts against the first separator of the next second unit.
[0057] As a preferred embodiment, the first current collector 11, the second current collector 23 and the third current collector 33 are all one of aluminum foil current collector, stainless steel foil current collector, titanium foil current collector or copper-aluminum composite foil current collector.
[0058] As a preferred embodiment, the thickness of the first current collector 11, the thickness of the second current collector 23 and the thickness of the third current collector 33 are all 5μm to 500μm (depending on the actual use needs, it can be 5μm, or 50μm, or 300μm, or 500μm, etc.).
[0059] As a preferred embodiment, the thickness of the first positive electrode layer 12 and the thickness of the second positive electrode layer 24 are both 20 μm to 2000 μm (depending on the actual use requirements, it can be 20 μm, or 200 μm, or 1000 μm, or 2000 μm, etc.).
[0060] As a preferred embodiment, the first positive electrode layer 12 and the second positive electrode layer 24 both contain the following components in mass percentage: 60% to 96% (depending on the actual needs, it can be 60%, or 75%, or 85%, or 96%, etc.) positive electrode active material, 2% to 5% (depending on the actual needs, it can be 2%, or 3%, or 4%, or 5%, etc.) a first conductive agent, 2% to 5% (depending on the actual needs, it can be 2%, or 3%, or 4%, or 5%, etc.) a first binder and 0% to 30% (depending on the actual needs, it can be 0.5%, or 5%, or 20%, or 30%, etc.) a first solid electrolyte.
[0061] As a preferred embodiment, when the bipolar soft-pack battery structure is a lithium-ion battery structure, the positive electrode active material is one or a mixture of at least two of ternary lithium, lithium iron phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium cobalt oxide, lithium manganese oxide and lithium-rich manganese-based materials;
[0062] When the bipolar soft-pack battery structure is a sodium ion battery structure, the positive electrode active material is one of polyanions, Prussian blue and oxides, or a mixture of at least two of them.
[0063] As a preferred embodiment, the first conductive agent is one or a mixture of at least two of Super P, LI-2080, 350G, acetylene black, carbon fiber VGCF, carbon nanotubes CNTs, Ketjen black, graphite conductive agent and graphene;
[0064] The first binder is one or a mixture of at least two of polyvinylidene fluoride (PVDF) and its modified materials, polyethylene oxide (PEO) and its modified materials, polymethyl methacrylate (PMMA) and its modified materials, polytetrafluoroethylene (PTFE), sodium carboxymethyl cellulose (CMC) and its modified materials, lithium carboxymethyl cellulose (CMC) and its modified materials, styrene-butadiene rubber (SBR) and its modified materials, and polyvinyl alcohol (PVA) and its modified materials;
[0065] The first solid electrolyte is one of an oxide solid electrolyte, a NASICON solid electrolyte, a sulfide solid electrolyte and a halide solid electrolyte, or a mixture of at least two of them.
[0066] As a preferred embodiment, the thickness of the first negative electrode layer 22 and the thickness of the second negative electrode layer 32 are both 20 μm to 2000 μm (depending on the actual use requirements, it can be 20 μm, or 200 μm, or 1000 μm, or 2000 μm, etc.).
[0067] As a preferred embodiment, the first negative electrode layer 22 and the second negative electrode layer 32 both contain the following components in percentage by mass: 60% to 96% (depending on the actual needs, it can be 60%, or 75%, or 85%, or 96%, etc.) of negative electrode active material, 2% to 5% (depending on the actual needs, it can be 2%, or 3%, or 4%, or 5%, etc.) of the second conductive agent, 2% to 5% (depending on the actual needs, it can be 2%, or 3%, or 4%, or 5%, etc.) of the second binder and 0% to 30% (depending on the actual needs, it can be 0.5%, or 5%, or 20%, or 30%, etc.) of the second solid electrolyte.
[0068] As a preferred embodiment, the negative electrode active material is one or a mixture of at least two of metallic lithium, graphite, silicon-based negative electrode, lithium titanate, metallic sodium, hard carbon or soft carbon;
[0069] The second conductive agent is one or a mixture of at least two of Super P, LI-2080, 350G, acetylene black, carbon fiber VGCF, carbon nanotubes CNTs, Ketjen black, graphite conductive agent and graphene;
[0070] The second binder is one or a mixture of at least two of polyvinylidene fluoride (PVDF) and its modified materials, polyethylene oxide (PEO) and its modified materials, polymethyl methacrylate (PMMA) and its modified materials, polytetrafluoroethylene (PTFE), sodium carboxymethyl cellulose (CMC) and its modified materials, lithium carboxymethyl cellulose (CMC) and its modified materials, styrene-butadiene rubber (SBR) and its modified materials, and polyvinyl alcohol (PVA) and its modified materials;
[0071] The second solid electrolyte is one or a mixture of at least two of an oxide solid electrolyte, a NASICON solid electrolyte, a sulfide solid electrolyte and a halide solid electrolyte.
[0072] As a preferred embodiment, the thickness of the first diaphragm 21 and the thickness of the second diaphragm 31 are both 5 μm to 500 μm (depending on the actual use requirements, it can be 5 μm, or 50 μm, or 300 μm, or 500 μm, etc.).
[0073] As a preferred embodiment, both the first separator 21 and the second separator 31 include a separator matrix A and a gel electrolyte 40 filled in the separator matrix A.
[0074] As a preferred embodiment, the diaphragm matrix A is one or a mixture of at least two of a PP diaphragm matrix, a PE diaphragm matrix and a glass fiber diaphragm matrix;
[0075] The gel electrolyte 40 is one of a polyacrylonitrile (PAN)-based gel electrolyte, a polymethyl methacrylate (PMMA)-based gel electrolyte, or a polyvinylidene fluoride (PVDF)-based gel electrolyte.
[0076] As a preferred embodiment, the electrolyte used in the bipolar soft-pack battery structure is a sodium ion gel electrolyte or a lithium ion gel electrolyte.
[0077] As a preferred embodiment, the length of the first negative electrode layer 22 / the second negative electrode layer 32 is 0.2mm~3mm longer than the length of the first positive electrode layer 12 / the second positive electrode layer 24 (depending on the actual use needs, it can be 0.2mm, or 0.8mm, or 2mm, or 3mm, etc.), and the width of the first negative electrode layer 22 / the second negative electrode layer 32 is 0.2mm~3mm wider than the width of the first positive electrode layer 12 / the second positive electrode layer 24 (depending on the actual use needs, it can be 0.2mm, or 0.8mm, or 2mm, or 3mm, etc.); in this embodiment of the present application, the first negative electrode layer and the second negative electrode layer have the same length and width, the first positive electrode layer and the second positive electrode layer have the same length and width, and the first separator and the second separator have the same length and width.
[0078] The length of the first separator 21 / the second separator 31 is 0.2mm~3mm longer than the length of the first negative electrode layer 22 / the second negative electrode layer 32 (depending on the actual needs, it can be 0.2mm, or 0.8mm, or 2mm, or 3mm, etc.), and the width of the first separator 21 / the second separator 31 is 0.2mm~3mm wider than the width of the first negative electrode layer 22 / the second negative electrode layer 32 (depending on the actual needs, it can be 0.2mm, or 0.8mm, or 2mm, or 3mm, etc.).
[0079] By controlling the length and width difference between the negative electrode layer and the positive electrode layer, and the length and width difference between the diaphragm and the negative electrode layer, there is no need to seal and separate the first current collector of the first unit and the second current collector close to the first unit, between two adjacent second current collectors, and between the second current collector and the third current collector close to the third unit. There is no need to seal between two adjacent battery cells, and there is good interface contact, which can achieve normal charging and discharging of the battery.
[0080] As a preferred embodiment, the first positive electrode layer, the second positive electrode layer, the first negative electrode layer and the second negative electrode layer are all self-supporting dry electrode films. In the embodiment of the present application, the binders used in the positive electrode layer and the negative electrode layer are all fiberizable binders, which can be fiberized during the dispersion process, so that the components of the positive electrode layer and the negative electrode layer are directly rolled to form a self-supporting dry electrode film during the mixing process, which is conducive to the infiltration of the positive electrode layer and the negative electrode layer by the gel electrolyte precursor, and can effectively maintain the formability of the positive electrode layer and the negative electrode layer.
[0081] As a preferred embodiment, the first positive electrode layer, the second positive electrode layer, the first negative electrode layer and the second negative electrode layer are all electrode layers infiltrated with a gel electrolyte precursor. In this way, there is no need to seal and separate the first current collector of the first unit and the second current collector close to the first unit, between two adjacent second current collectors, and between the second current collector and the third current collector close to the third unit, and there is no need to seal between two adjacent battery cells, so that there is good interface contact and normal charging and discharging of the battery can be achieved.
[0082] The gel electrolyte precursor is one of a polyacrylonitrile-based gel electrolyte precursor, a polymethyl methacrylate-based gel electrolyte precursor, and a polyvinylidene fluoride-based gel electrolyte precursor.
[0083] The voltage of bipolar batteries is relatively high. Once there is a problem of liquid channeling, the electrolyte will be subjected to high voltage (the electrolyte on the market can only withstand a voltage of 5V) and the problem of electrolyte decomposition will occur; after the electrolyte decomposition, it will further affect the performance of the bipolar battery. In the structure of the present application, by using a diaphragm filled with gel electrolyte, and a positive electrode layer and a negative electrode layer soaked in a gel electrolyte precursor, liquid channeling between the positive and negative electrodes of the battery can be prevented, thereby effectively avoiding the problem of electrolyte decomposition caused by electrolyte channeling; at the same time, it can make it possible to make it possible for the first current collector of the first unit and the second current collector close to the first unit, between two adjacent second current collectors, and between the second current collector and the third current collector close to the third unit to be sealed and separated, and there is no need to seal between two adjacent battery cells, with good interface contact, and normal charging and discharging of the battery can be achieved.
[0084] On the other hand, an embodiment of the present invention also provides a method for preparing the bipolar soft-pack battery structure, which comprises at least the following steps: in an inert gas atmosphere, immersing the diaphragm matrix in a gel electrolyte precursor, and after the diaphragm matrix is soaked, taking out the diaphragm matrix and encapsulating it to obtain an encapsulated diaphragm matrix; heating the encapsulated diaphragm matrix to obtain a first diaphragm / second diaphragm.
[0085] As a preferred embodiment, the inert gas is argon; the packaging is performed by an aluminum-plastic film; the heating is performed at 70°C to 85°C for 2h to 3h, preferably at 70°C for 2h. By heating, the gel electrolyte precursor is polymerized to form a gel electrolyte. Infiltration generally refers to that the diaphragm matrix is fully filled with the gel electrolyte precursor.
[0086] As a preferred embodiment, the method for preparing the bipolar soft-pack battery structure further includes the following steps: preparing a first unit: welding a first electrode tab on one side of a first current collector, and providing a first positive electrode layer on the other side of the first current collector to obtain a first unit;
[0087] Prepare a second unit: arrange a second positive electrode layer on one side of a second current collector, arrange a first negative electrode layer on the other side of the second current collector, and arrange a first separator on the side of the first negative electrode layer away from the second current collector to obtain a second unit;
[0088] Prepare a third unit: weld a second electrode tab on one side of a third current collector, arrange a second negative electrode layer on the other side of the third current collector, and arrange a second separator on the side of the second negative electrode layer away from the third current collector to obtain a third unit;
[0089] The first unit, the second unit and the third unit are stacked in sequence, the first separator is in contact with the first positive electrode layer, the second separator is in contact with the second positive electrode layer, and then packaged and heated to obtain a bipolar soft-pack battery structure.
[0090] As a preferred embodiment, the packaging is performed by an aluminum-plastic film; the heating is performed at 70° C. to 85° C. for 2 h to 3 h, preferably at 70° C. for 2 h.
[0091] Example 1
[0092] Preparation of the first diaphragm / second diaphragm: Under an argon atmosphere, the glass fiber diaphragm is immersed in the gel electrolyte precursor, and after being fully infiltrated, it is packaged with an aluminum-plastic film and then heated at 70° C. for 2 h to obtain the first diaphragm / second diaphragm.
[0093] Preparation of the first positive electrode layer / second positive electrode layer: lithium iron phosphate positive electrode material (dry powder mass fraction 72%), polytetrafluoroethylene binder (dry powder mass fraction 3%), conductive carbon (SP dry powder mass fraction 3%, carbon nanotube mass fraction 2%) and LATP solid electrolyte (20% mass fraction) are mixed evenly, and then the polytetrafluoroethylene is fiberized under the action of shear force to obtain a fiberized powder mixture; the fiberized powder mixture is rolled (to form a self-supporting film) to obtain a first positive electrode layer / second positive electrode layer with a thickness of 0.4-0.6 mm, and a gel electrolyte precursor is dripped (in an argon atmosphere) on the first positive electrode layer / second positive electrode layer to fully infiltrate it for standby use.
[0094] Preparation of the first negative electrode layer / second negative electrode layer: lithium titanate negative electrode material (dry powder mass fraction 72%), polytetrafluoroethylene binder (dry powder mass fraction 3%), conductive carbon (SP dry powder mass fraction 5%) and LATP solid electrolyte (20% mass fraction) are mixed evenly, and then the polytetrafluoroethylene is fiberized under the action of shear force to obtain a fiberized powder mixture; the fiberized powder mixture is rolled (to form a self-supporting film) to obtain a first negative electrode layer / second negative electrode layer with a thickness of 0.4-0.6 mm, and a gel electrolyte precursor is dripped (in an argon atmosphere) on the first negative electrode layer / second negative electrode layer to fully infiltrate it for standby use.
[0095] The method for preparing the bipolar soft-pack battery structure comprises the following steps:
[0096] Prepare a first unit: weld a first electrode tab on one side of a first current collector, and arrange a first positive electrode layer on the other side of the first current collector to obtain a first unit;
[0097] Prepare a second unit: arrange a second positive electrode layer on one side of a second current collector, arrange a first negative electrode layer on the other side of the second current collector, and arrange a first separator on the side of the first negative electrode layer away from the second current collector to obtain a second unit;
[0098] Prepare a third unit: weld a second electrode tab on one side of a third current collector, arrange a second negative electrode layer on the other side of the third current collector, and arrange a second separator on the side of the second negative electrode layer away from the third current collector to obtain a third unit;
[0099] The first unit, the second unit and the third unit are stacked in sequence, the first separator is in contact with the first positive electrode layer, the second separator is in contact with the second positive electrode layer, and then packaged with an aluminum-plastic film and heated at 70° C. for 2 hours to obtain a bipolar soft-pack battery structure.
[0100] Example 2
[0101] Preparation of the first diaphragm / second diaphragm: Under an argon atmosphere, the glass fiber diaphragm is immersed in the gel electrolyte precursor, and after being fully infiltrated, it is packaged with an aluminum-plastic film and then heated at 70° C. for 2 h to obtain the first diaphragm / second diaphragm.
[0102] Preparation of the first positive electrode layer / second positive electrode layer: lithium iron phosphate positive electrode material (dry powder mass fraction 72%), polytetrafluoroethylene binder (dry powder mass fraction 3%), conductive carbon (SP dry powder mass fraction 3%, carbon nanotube mass fraction 2%) and LATP solid electrolyte (20% mass fraction) are mixed evenly, and then the polytetrafluoroethylene is fiberized under the action of shear force to obtain a fiberized powder mixture; the fiberized powder mixture is rolled (to form a self-supporting film) to obtain a first positive electrode layer / second positive electrode layer with a thickness of 0.4-0.6 mm, and a gel electrolyte precursor is dripped (in an argon atmosphere) on the first positive electrode layer / second positive electrode layer to fully infiltrate it for standby use.
[0103] Preparation of the first negative electrode layer / second negative electrode layer: uniformly mix graphite negative electrode material (dry powder mass fraction 72%), polytetrafluoroethylene binder (dry powder mass fraction 3%), conductive carbon (SP dry powder mass fraction 5%) and LLZO solid electrolyte (20% mass fraction), and then fiberize the polytetrafluoroethylene under the action of shear force to obtain a fiberized powder mixture; roll the fiberized powder mixture (to form a self-supporting film) to obtain a first negative electrode layer / second negative electrode layer with a thickness of 0.4-0.6 mm, and drip (argon atmosphere) a gel electrolyte precursor on the first negative electrode layer / second negative electrode layer to fully infiltrate it for standby use.
[0104] The method for preparing the bipolar soft-pack battery structure comprises the following steps:
[0105] Prepare a first unit: weld a first electrode tab on one side of a first current collector, and arrange a first positive electrode layer on the other side of the first current collector to obtain a first unit;
[0106] Prepare a second unit: arrange a second positive electrode layer on one side of a second current collector, arrange a first negative electrode layer on the other side of the second current collector, and arrange a first separator on the side of the first negative electrode layer away from the second current collector to obtain a second unit;
[0107] Prepare a third unit: weld a second electrode tab on one side of a third current collector, arrange a second negative electrode layer on the other side of the third current collector, and arrange a second separator on the side of the second negative electrode layer away from the third current collector to obtain a third unit;
[0108] The first unit, five second units and the third unit are stacked in sequence, the first separator is in contact with the first positive electrode layer, the second separator is in contact with the second positive electrode layer, and then packaged with an aluminum-plastic film and heated at 70° C. for 2 hours to obtain a bipolar soft-pack battery structure.
[0109] Comparative Example 1
[0110] Preparation of positive electrode layer: lithium iron phosphate positive electrode material (dry powder mass fraction 92%), polytetrafluoroethylene binder (dry powder mass fraction 3%), conductive carbon (SP dry powder mass fraction 3%) and carbon nanotube mass fraction 2%) are mixed evenly, and then the polytetrafluoroethylene is fiberized under the action of shear force to obtain a fiberized powder mixture; the fiberized powder mixture is rolled to form a self-supporting film to obtain a positive electrode layer with a thickness of 0.4-0.6mm, and a gel electrolyte precursor is dripped on the positive electrode layer (argon atmosphere) to fully infiltrate it for use.
[0111] Preparation of negative electrode layer: Mix graphite negative electrode material (dry powder mass fraction 92%), polytetrafluoroethylene binder (dry powder mass fraction 3%) and conductive carbon (SP dry powder mass fraction 5%) evenly, and then fiberize polytetrafluoroethylene under the action of shear force to obtain a fiberized powder mixture; roll the fiberized powder mixture to form a self-supporting film to obtain a negative electrode layer with a thickness of 0.4-0.6mm for standby use.
[0112] Preparation of the diaphragm layer: Under an argon atmosphere, immerse the glass fiber diaphragm in the gel electrolyte precursor. After being fully wetted, encapsulate it with an aluminum plastic film and heat it at 70°C for 2h to polymerize the gel electrolyte precursor to obtain a diaphragm layer for later use.
[0113] The method for making a bipolar structure soft pack battery is as follows:
[0114] Preparation of unit a: welding the tabs on the current collector, compounding the positive electrode layer with the current collector, dripping (argon atmosphere) the gel electrolyte precursor on the positive electrode layer to fully infiltrate it, and obtaining unit a for standby use;
[0115] Preparation of unit b: Compound the positive and negative electrode layers on the front and back sides of the same current collector, drip (argon atmosphere) gel electrolyte precursor on the positive and negative electrode layers to fully infiltrate them, and then set a separator layer on the side of the negative electrode layer away from the current collector to obtain unit b;
[0116] Preparation of unit c: welding the tabs on the current collector, compounding the negative electrode layer with the current collector, dripping (argon atmosphere) the gel electrolyte precursor on the negative electrode layer to fully infiltrate it, and setting aside;
[0117] Assemble the a, b, and c units in the order of a unit, n b units, and c unit. Assemble the inside of the battery in the order of positive electrode, separator, and negative electrode. After assembly, use aluminum-plastic film to package and heat at 70°C for 2h to obtain a bipolar structure soft-pack battery.
[0118] Comparative Example 2
[0119] Preparation of positive electrode layer: lithium iron phosphate positive electrode material (dry powder mass fraction 92%), polytetrafluoroethylene binder (dry powder mass fraction 3%) and conductive carbon (SP dry powder mass fraction 3%, carbon nanotube mass fraction 2%) are mixed evenly, and then polytetrafluoroethylene is fiberized under the action of shear force to obtain a fiberized powder mixture; the fiberized powder mixture is rolled to form a self-supporting film with a thickness of 0.8-1.0mm, and a gel electrolyte precursor is dripped on the positive electrode layer (argon atmosphere) to fully infiltrate it for use.
[0120] Preparation of negative electrode layer: Mix graphite negative electrode material (dry powder mass fraction 92%), polytetrafluoroethylene binder (dry powder mass fraction 3%) and conductive carbon (SP dry powder mass fraction 5%) evenly, and then fiberize polytetrafluoroethylene under the action of shear force to obtain a fiberized powder mixture; roll the fiberized powder mixture to form a self-supporting film with a thickness of 0.8-1.0 mm for standby use.
[0121] Preparation of the diaphragm layer: Under an argon atmosphere, immerse the glass fiber diaphragm in the gel electrolyte precursor. After fully absorbing the liquid, package it with an aluminum plastic film, heat it at 70°C for 2h to polymerize the gel electrolyte precursor, and set it aside.
[0122] The method for making a bipolar structure soft pack battery is as follows:
[0123] Preparation of unit a: welding the tabs on the current collector, compounding the positive electrode layer with the current collector, dripping (argon atmosphere) the gel electrolyte precursor on the positive electrode layer to fully infiltrate it, and setting aside;
[0124] Preparation of unit b: Compound the positive and negative electrode layers on the positive and negative sides of the same current collector, drip (argon atmosphere) gel electrolyte precursor on the positive and negative electrode layers to fully infiltrate them, and then set a separator layer on the negative electrode layer;
[0125] Preparation of unit c: welding the tabs on the current collector, compounding the negative electrode layer with the current collector, dripping (argon atmosphere) the gel electrolyte precursor on the negative electrode layer to fully infiltrate it, and setting aside;
[0126] Assemble the a, b, and c units in the order of a unit, n b units, and c unit. Assemble the inside of the battery in the order of positive electrode, separator, and negative electrode. After assembly, use aluminum-plastic film to package and heat at 70°C for 2h to obtain a bipolar structure soft-pack battery.
[0127] Comparative Example 3
[0128] Preparation of positive electrode layer: lithium iron phosphate positive electrode material (dry powder mass fraction 92%), polytetrafluoroethylene binder (dry powder mass fraction 3%) and conductive carbon (SP dry powder mass fraction 3%, carbon nanotube mass fraction 2%) are mixed evenly, and then polytetrafluoroethylene is fiberized under the action of shear force to obtain a fiberized powder mixture; the fiberized powder mixture is rolled to form a self-supporting film with a thickness of 0.8-1.0mm, and a gel electrolyte precursor is dripped on the positive electrode layer (argon atmosphere) to fully infiltrate it for use.
[0129] Preparation of negative electrode layer: Mix graphite negative electrode material (dry powder mass fraction 92%), polytetrafluoroethylene binder (dry powder mass fraction 3%) and conductive carbon (SP dry powder mass fraction 5%) evenly, and then fiberize polytetrafluoroethylene under shear force to obtain a fiberized powder mixture; roll the fiberized powder mixture to form a self-supporting film with a thickness of 0.4-0.6mm for standby use.
[0130] Preparation of the diaphragm layer: Under an argon atmosphere, PE diaphragm is immersed in the gel electrolyte precursor. After being fully infiltrated, it is packaged with an aluminum plastic film and heated at 70° C. for 2 h to polymerize the gel electrolyte precursor for use.
[0131] The method for making a bipolar structure soft pack battery is as follows:
[0132] Preparation of unit a: welding the tabs on the current collector, compounding the positive electrode layer with the current collector, dripping (argon atmosphere) the gel electrolyte precursor on the positive electrode layer to fully infiltrate it, and setting aside;
[0133] Preparation of unit b: Compound the positive and negative electrode layers on the positive and negative sides of the same current collector, drip (argon atmosphere) gel electrolyte precursor on the positive and negative electrode layers to fully infiltrate them, and then set a separator layer on the negative electrode layer;
[0134] Preparation of unit c: welding the tabs on the current collector, compounding the negative electrode layer with the current collector, dripping (argon atmosphere) the gel electrolyte precursor on the negative electrode layer to fully infiltrate it, and setting aside;
[0135] Assemble the a, b, and c units in the order of a unit, n b units, and c unit. Assemble the inside of the battery in the order of positive electrode, separator, and negative electrode. After assembly, use aluminum-plastic film to package and heat at 70°C for 2h to obtain a bipolar structure soft-pack battery.
[0136] Table 1 below is a comparison of the material differences and results between Examples 1-2 and Comparative Examples 1-3. As can be seen from Table 1, the bipolar soft-pack battery structure obtained in the examples of the present application has good positive electrode gram capacity, first efficiency and 100-week capacity retention rate.
[0137] Table 1 Comparison of material differences and performance test results between Examples 1-2 and Comparative Examples 1-3
[0138]
[0139] In the description of this specification, the description with reference to the terms "an embodiment", "example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example.
[0140] In addition, it should be understood that although this specification is described according to implementation methods, not every implementation method contains only one independent technical solution. This narrative method of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation methods that can be understood by those skilled in the art.
[0141] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A bipolar soft pack battery structure, characterized in that: comprising a first unit, at least one second unit, and a third unit, wherein the second unit is arranged between the first unit and the third unit; The first unit includes a first current collector and a first positive electrode layer that are arranged in contact with each other, and the first positive electrode layer is arranged close to the second unit; The second unit includes a first separator, a first negative electrode layer, a second current collector and a second positive electrode layer which are sequentially abutted; the first separator abuts the first positive electrode layer, and the second positive electrode layer is arranged close to the third unit; The third unit comprises a second separator, a second negative electrode layer and a third current collector which are sequentially abutted; the second separator abuts the second positive electrode layer; The first separator and the second separator are both separators filled with gel electrolyte.
2. The bipolar soft pack battery structure according to claim 1, characterized in that: The first current collector, the second current collector and the third current collector are all selected from the group consisting of an aluminum foil current collector, a stainless steel foil current collector, a titanium foil current collector and a copper-aluminum composite foil current collector; The thickness of the first current collector, the thickness of the second current collector and the thickness of the third current collector are all 5 μm to 500 μm; The first positive electrode layer, the second positive electrode layer, the first negative electrode layer and the second negative electrode layer are all electrode layers impregnated with a gel electrolyte precursor.
3. The bipolar soft pack battery structure according to claim 1, characterized in that: The thickness of the first positive electrode layer and the thickness of the second positive electrode layer are both 20 μm to 2000 μm; The first positive electrode layer and the second positive electrode layer each contain the following components by mass percentage: 60% to 96% positive electrode active material, 2% to 5% first conductive agent, 2% to 5% first binder and 0% to 30% first solid electrolyte; When the bipolar soft-pack battery structure is a lithium-ion battery structure, the positive electrode active material is one or a mixture of at least two of ternary lithium, lithium iron phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium cobalt oxide, lithium manganese oxide and lithium-rich manganese-based materials; When the bipolar soft-pack battery structure is a sodium ion battery structure, the positive electrode active material is one or a mixture of at least two of polyanions, Prussian blue and oxides; The first conductive agent is one or a mixture of at least two of Super P, LI-2080, 350G, acetylene black, carbon fiber VGCF, carbon nanotubes CNTs, Ketjen black, graphite conductive agent and graphene; The first binder is one or a mixture of at least two of polyvinylidene fluoride and its modified materials, polyethylene oxide and its modified materials, polymethyl methacrylate and its modified materials, polytetrafluoroethylene, sodium carboxymethyl cellulose and its modified materials, lithium carboxymethyl cellulose and its modified materials, styrene-butadiene rubber and its modified materials, and polyvinyl alcohol and its modified materials; The first solid electrolyte is one of an oxide solid electrolyte, a NASICON solid electrolyte, a sulfide solid electrolyte and a halide solid electrolyte, or a mixture of at least two of them.
4. The bipolar soft pack battery structure according to claim 1, characterized in that: The thickness of the first negative electrode layer and the thickness of the second negative electrode layer are both 20 μm to 2000 μm; The first negative electrode layer and the second negative electrode layer each contain the following components by mass percentage: 60% to 96% of negative electrode active material, 2% to 5% of a second conductive agent, 2% to 5% of a second binder and 0% to 30% of a second solid electrolyte; The negative electrode active material is one or a mixture of at least two of metallic lithium, graphite, silicon-based negative electrode, lithium titanate, metallic sodium, hard carbon or soft carbon; The second conductive agent is one or a mixture of at least two of Super P, LI-2080, 350G, acetylene black, carbon fiber VGCF, carbon nanotubes CNTs, Ketjen black, graphite conductive agent and graphene; The second binder is one or a mixture of at least two of polyvinylidene fluoride and its modified materials, polyethylene oxide and its modified materials, polymethyl methacrylate and its modified materials, polytetrafluoroethylene, sodium carboxymethyl cellulose and its modified materials, lithium carboxymethyl cellulose and its modified materials, styrene-butadiene rubber and its modified materials, and polyvinyl alcohol and its modified materials; The second solid electrolyte is one or a mixture of at least two of an oxide solid electrolyte, a NASICON solid electrolyte, a sulfide solid electrolyte and a halide solid electrolyte.
5. The bipolar soft pack battery structure according to claim 1, characterized in that: The thickness of the first diaphragm and the thickness of the second diaphragm are both 5 μm to 500 μm; The first separator and the second separator each include a separator matrix and a gel electrolyte filled in the separator matrix.
6. The bipolar soft pack battery structure according to claim 5, characterized in that: The diaphragm matrix is one or a mixture of at least two of a PP diaphragm matrix, a PE diaphragm matrix and a glass fiber diaphragm matrix; The gel electrolyte is one of a polyacrylonitrile-based gel electrolyte, a polymethyl methacrylate-based gel electrolyte, or a polyvinylidene fluoride-based gel electrolyte; The electrolyte used in the bipolar soft-pack battery structure is a sodium ion gel electrolyte or a lithium ion gel electrolyte.
7. The bipolar soft pack battery structure according to claim 1, characterized in that: The length of the first negative electrode layer / the second negative electrode layer is 0.2 mm to 3 mm longer than the length of the first positive electrode layer / the second positive electrode layer, and the width of the first negative electrode layer / the second negative electrode layer is 0.2 mm to 3 mm wider than the width of the first positive electrode layer / the second positive electrode layer; The length of the first separator / the second separator is 0.2 mm to 3 mm longer than the length of the first negative electrode layer / the second negative electrode layer, and the width of the first separator / the second separator is 0.2 mm to 3 mm wider than the width of the first negative electrode layer / the second negative electrode layer.
8. The method for preparing the bipolar soft-pack battery structure according to any one of claims 1 to 7, characterized in that: The method comprises at least the following steps: immersing a diaphragm matrix in a gel electrolyte precursor in an inert gas atmosphere, taking out and packaging the diaphragm matrix after the diaphragm matrix is soaked to obtain a packaged diaphragm matrix; and heating the packaged diaphragm matrix to obtain a first diaphragm / a second diaphragm.
9. The bipolar soft pack battery structure according to claim 8, characterized in that: The inert gas is argon; the packaging is performed by an aluminum-plastic film; and the heating is performed at 70° C. to 85° C. for 2 h to 3 h.
10. The bipolar soft pack battery structure according to claim 8, characterized in that: The method for preparing the bipolar soft-pack battery structure further includes the following steps: preparing a first unit: welding a first electrode tab on one side of a first current collector, and providing a first positive electrode layer on the other side of the first current collector to obtain a first unit; Prepare a second unit: arrange a second positive electrode layer on one side of a second current collector, arrange a first negative electrode layer on the other side of the second current collector, and arrange a first separator on the side of the first negative electrode layer away from the second current collector to obtain a second unit; Prepare a third unit: weld a second electrode tab on one side of a third current collector, arrange a second negative electrode layer on the other side of the third current collector, and arrange a second separator on the side of the second negative electrode layer away from the third current collector to obtain a third unit; The first unit, the second unit and the third unit are stacked in sequence, the first separator is in contact with the first positive electrode layer, the second separator is in contact with the second positive electrode layer, and then packaged and heated to obtain a bipolar soft-pack battery structure; The packaging is performed by an aluminum-plastic film; the heating is performed at 70° C. to 85° C. for 2 h to 3 h; The first positive electrode layer, the second positive electrode layer, the first negative electrode layer and the second negative electrode layer are all self-supporting dry electrode films.
